Faktor-faktor Resiko Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Tanjung Batu Kabupaten Ogan Ilir Tahun 2024 - Rosy, Reviny; Afrika, Eka; Ernawati, Wahyu; Dewi, Ratna (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The child health problem that is currently the main priority that the government wants to improve is regarding child growth and development. Stunting is a form of malnutrition that reflects long-term cumulative malnutrition. According to WHO, the prevalence of short toddlers becomes a public health problem if the prevalence is 20% or more. The prevalence of stunted toddlers in Indonesia is still more than (24.4%) Results of a study on the nutritional status of Indonesian districts/cities in 2022, the prevalence of stunted toddlers (height for age) based on districts/cities in West Sumatra Province with a stunting rate of 33.8% , According to the Ministry of Health 2018, more than 1/3 or 9 million Indonesian toddlers experience stunting. The aim of this research is to determine the relationship between knowledge, exclusive breastfeeding, complementary feeding, and economic status with the incidence of stunting in toddlers aged 24-60 months in Tanjung Batu Community Health Center, Ogan Ilir Regency, 2024. Type and Design: Quantitative research using analytical survey methods with a cross sectional approach. The population in this study were all mothers who checked the health of their toddlers at the Tanjung Batu Community Health Center, totaling 152 respondents. The sample used was 60 respondents. The results of univariate analysis from 60 respondents showed that 9 respondents (15.0%) experienced stunting and 51 respondents (85.0%) did not. The results of the chi-square statistical test for the variable giving MP ASI were found to be ρ value = 0.026, the variable giving exclusive breast milk was found to be ρ value = 0.045 and the variable family economic status was found to be ρ value = 0.035 which is smaller than α=0.05 indicating there is a significant relationship. Giving MP Breast milk and the incidence of stunting in toddlers aged 24-60 months at the Tanjung Batu Babupaten Ogan Ilir Community Health Center in 2024